Probiotic supplementation with Lactobacillus casei in sows and its effects on the zootechnical parameters of piglets - Suárez, Rafael (2019)
The aim of this study was to evaluate the supplementation of Lactobacillus casei in sows and its effect on the zootechnical parameters of piglets. A total of 18 F1 Landrace x Large White sows were distributed in three completely randomized groups: control and two groups supplemented with L. casei (T1: 10 x 106 CFU [colony forming units]; T2: 10 x108 CFU). The doses were administered weekly orally 2 h after the first feeding of the day (09:00) for 180 days, covering a productive cycle. Results of zootechnical variables of each female and her piglets at the peripartum, at weaning and at the new service of the female were evauated. In the peripartum, a greater mean body weight of total births (PPNT) and average birth body weight were found (PPNV) in the supplemented animals compared to the control group (p<0.05). In the lactation phase there was a greater total weight per litter at weaning (PTCD), mean body weight per piglet at weaning (PPLD), total body weight gain per litter per sow (GTCDH), mean total body weight per piglet (GTPL) and mean body weight per day pero piglet (GPLD) in the animals supplemented with the probiotic compared to the control group (p<0.01). None of the variables showed differences between the supplemented groups. It is concluded that oral supplementation with the probiotic Lactobacillus casei in the sows during the gestation and lactation phase improves the productive indexes in the peripartum period and in the lactation phase of the piglets.